Faktor-Faktor yang Memengaruhi Keputusan Petani dalam Mengikuti Asuransi Usaha Tani Padi (AUTP) di Kecamatan Buay Madang Timur - Niswatuwarohmah, N; Munajat, M; Sari, Yunita (SAFE-Network, 2024)
This research aims to analyze the factors that influence farmers' decisions to take part in rice farming insurance (AUTP) in East Buay Madang District. The type of research used in this research is a quantitative descriptive method. The data analysis used in this research is multiple regression analysis. The results of the research show that the factors of farming experience, land area, number of family members, age of farmer, level of education, role of instructor, income from rice farming, claim success, level of difficulty in registering and claiming have a significant influence on farmers' decisions in participating in the Rice Farming Insurance (AUTP) program. in East Buay Madang District, East Ogan Komering Ulu Regency. The factor that most influences farmers' decisions in participating in the Rice Farming Insurance (AUTP) program in East Buay Madang District, East Ogan Komering Ulu Regency is the role of extension workers with a standard value of the partial regression coefficient of 6.049.